(untitled) (Balneo and PRM Research Journal, 2022)
Abstract: Introduction. The number of non-communicable diseases (NCDs) is in a constant rise, especially in the low and middle income countries. They could be highly prevented by implementing programs that will help in promoting health and changing harmful behaviors. The aim of this paper is to show that Rebound exercisesis a great example of such physical activity. Material and method. The study plan was designed to asses both physical and functional explorations, ultrasound scans, self-perception of body image and laboratory parameters for each patient. A total of 64 parameters were analyzed: 44 anthropometric parameters and 20 body composition parameters from 80 participants. The subjects were analyzed for a period of 6 months. Results and discussions. Parameters were analyzed at the beginning of the study (07.02.2019), after 3 months (25.05.2019) and at the end (26.09.2019). The results showed improvements in all utilized parameters. Conclusions. This study offers a novel perspective on Kangoo jumps practice. People with spine problems, diabetes, overweight levels, improved their health, got rid of back pain, lost weight and had a more toned body.